Дослідження моделей знм для ідентифікації домашніх тварин - Гурська, В. В. (ХНУРЕ, 2021)
The problem of creating a model of a convolutional neural network for the identification of domestic animals was analyzed. Analogues on the market were considered, such as applications from Siwalu software, Dog Breed Camera from Manfred Breede and visual search from Microsoft. Also, relevance and purpose of the research were described.
Науковий керівник – д.т.н., проф. Смеляков К.С.
Keywords: моделі ЗНМ; ідентифікація тварин